NAC and Vitamin D Restore CNS Glutathione in Endotoxin-Sensitized Neonatal Hypoxic-Ischemic Rats - Lauren E. Adams; Hunter G. Moss; Danielle W. Lowe; Truman Brown; Donald B. Wiest; Bruce W. Hollis; Inderjit Singh; Dorothea D. Jenkins (MDPI AG, 2021)
Therapeutic hypothermia does not improve outcomes in neonatal hypoxia ischemia (HI) complicated by perinatal infection, due to well-described, pre-existing oxidative stress and neuroinflammation that shorten the therapeutic window. For effective neuroprotection post-injury, we must first define and then target CNS metabolomic changes immediately after endotoxin-sensitized HI (LPS-HI). We hypothesized that LPS-HI would acutely deplete reduced glutathione (GSH), indicating overwhelming oxidative stress in spite of hypothermia treatment in neonatal rats. Post-natal day 7 rats were randomized to sham ligation, or severe LPS-HI (0.5 mg/kg 4 h before right carotid artery ligation, 90 min 8% O2), followed by hypothermia alone or with N-acetylcysteine (25 mg/kg) and vitamin D (1,25(OH)2D3, 0.05 μg/kg) (NVD). We quantified in vivo CNS metabolites by serial 7T MR Spectroscopy before, immediately after LPS-HI, and after treatment, along with terminal plasma drug concentrations. GSH was significantly decreased in all LPS-HI rats compared with baseline and sham controls. Two hours of hypothermia alone did not improve GSH and allowed glutamate + glutamine (GLX) to increase. Within 1 h of administration, NVD increased GSH close to baseline and suppressed GLX. The combination of NVD with hypothermia rapidly improved cellular redox status after LPS-HI, potentially inhibiting important secondary injury cascades and allowing more time for hypothermic neuroprotection.